Cigarette smoke augments CSF3 expression in neutrophils to compromise alveolar–capillary barrier function during influenza infection. Issue 2 (25th August 2022) - McGrath, Joshua J.C.; Vanderstocken, Gilles; Dvorkin-Gheva, Anna; Cass, Steven P.; Afkhami, Sam; Fantauzzi, Matthew F.; Thayaparan, Danya; Reihani, Amir; Wang, Peiyao; Beaulieu, Ashley; Shen, Pamela; Morissette, Mathieu; et al.
Background: Cigarette smokers are at increased risk of acquiring influenza, developing severe disease and requiring hospitalisation/intensive care unit admission following infection. However, immune mechanisms underlying this predisposition are incompletely understood, and therapeutic strategies for influenza are limited. Methods: We used a mouse model of concurrent cigarette smoke exposure and H1N1 influenza infection, colony-stimulating factor (CSF)3 supplementation/receptor (CSF3R) blockade and single-cell RNA sequencing (scRNAseq) to investigate this relationship. Results: Cigarette smoke exposure exacerbated features of viral pneumonia such as oedema, hypoxaemia and pulmonary neutrophilia. Smoke-exposed infected mice demonstrated an increase in viral (v)RNA, but not replication-competent viral particles, relative to infection-only controls. Interstitial rather than airspace neutrophilia positively predicted morbidity in smoke-exposed infected mice. Screening of pulmonary cytokines using a novel dysregulation score identified an exacerbated expression of CSF3 and interleukin-6 in the context of smoke exposure and influenza. Recombinant (r)CSF3 supplementation during influenza aggravated morbidity, hypothermia and oedema, while anti-CSF3R treatment of smoke-exposed infected mice improved alveolar–capillary barrier function. scRNAseq delineated a shift in the distribution of Csf3 + cells towards neutrophils in the context of cigarette smoke and influenza. However, although smoke-exposed lungs were enriched for infected, highly activated neutrophils, gene signatures of these cells largely reflected an exacerbated form of typical influenza with select unique regulatory features. Conclusion: This work provides novel insight into the mechanisms by which cigarette smoke exacerbates influenza infection, unveiling potential therapeutic targets ( e.g. excess vRNA accumulation, oedematous CSF3R signalling) for use in this context, and potential limitations for clinical rCSF3 therapy during viral infectious disease. Cigarette smoke exacerbates PFU-independent viral RNA accumulation, morbidity-associated interstitial neutrophilia, Csf3 -expressing neutrophil recruitment and CSF3-mediated alveolar–capillary barrier dysregulation during influenza infection in mice https://bit.ly/3HVOuiw